A REVIEW ON QUASICCRYSTALS: CRYSTALS APERIODIC. - Landauro S., C. V. (2011)
In this paper a review of quasicrystals in a very particular point of view, is not intended to be comprehensive or detailed, where the state of the art knowledge of quasicrystals is presented from its discovery to its manipulation at the nanoscale is.